2014
DOI: 10.1111/cea.12264
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for dendritic cells in vernal keratoconjunctivitis: analysis by laser scanning confocal microscopy

Abstract: In vivo confocal microscopy appears to be a valuable tool in evaluating the dynamic change of DCs at the conjunctiva and cornea. DCs play an essential role in VKC and therefore may constitute a target for therapeutic intervention for VKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
7
25
1
Order By: Relevance
“…Montan et al [2] found that conjunctival biopsy specimens taken from patients with VKC showed higher counts for dendritic cell markers, including HLA-DR (MHC class II), FcεRI, and CD1a, than in healthy control subjects. Large numbers of dendritic cells distributed in the bulbar conjunctiva, limbus, and peripheral cornea of VKC have also been discovered on in vivo confocal microscopy [23]. Dendritic cells are crucial in determining the nature of an allergic response and are believed to play a major role in the pathogenesis of VKC [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Montan et al [2] found that conjunctival biopsy specimens taken from patients with VKC showed higher counts for dendritic cell markers, including HLA-DR (MHC class II), FcεRI, and CD1a, than in healthy control subjects. Large numbers of dendritic cells distributed in the bulbar conjunctiva, limbus, and peripheral cornea of VKC have also been discovered on in vivo confocal microscopy [23]. Dendritic cells are crucial in determining the nature of an allergic response and are believed to play a major role in the pathogenesis of VKC [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of dendritic cells distributed in the bulbar conjunctiva, limbus, and peripheral cornea of VKC have also been discovered on in vivo confocal microscopy [23]. Dendritic cells are crucial in determining the nature of an allergic response and are believed to play a major role in the pathogenesis of VKC [23][24][25]. Tacrolimus is a potent immunosuppressive agent, which causes marked suppression of the production of various cytokines by the activated T cells involved in the pathogenesis of VKC [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendritic cells, as antigen presenting cells, are critically involved in autoimmune disease,14 which makes it crucial to have careful control/rational use of topical and systemic immunosuppressive agents after successful surgery. In vivo confocal microscopy (IVCM), a non-invasive, real-time observing approach, can provide dynamic density changes of dendritic cells in vernal keratoconjunctivitis 15. IVCM was used in this study to monitor the density changes of dendritic cells in corneal grafts after modified LK, to guide the usage of corticosteroids and immunosuppressants, and to help reduce the recurrence of malignant Mooren's ulcer.…”
Section: Introductionmentioning
confidence: 99%